Combined heat and power plants integrated with carbon capture: Process and system level potential - Ahlmén, Madeleine; Hellsberg, Jesper (My University, 2020)
The world has expressed a strong desire to mitigate climate change during the past decades. In Sweden, the government has expressed the aims to achieve negative carbon emissions, Carbon Capture and Storage (CCS) is one of the key technologies in reaching this goal. This thesis determines the national potential for carbon capture in the Swedish waste and biomass fired Combined Heat and Power (CHP) plants. The effects on plant performance and the operation of connected district heating systems are evaluated. The evaluation was performed by developing CHP plant process models of all 110 Swedish CHP plants based on plant data. Each model was retrofitted with postcombustion carbon capture units with a 90 % capture rate of plant carbon dioxide emissions. A district heating system dispatch model was created and incorporated with the process models. The operating profiles of each plant was estimated based on the heat demand within each district heating network. Four strategies for operating the CHP plants were evaluated, based on the fuel consumption, district heating delivery and electricity generation relative to the amount of carbon captured. The results of the evaluation showed that the Swedish CHP plants alone have the potential, if equipped with CCS, of reaching Sweden’s goal of 11 Mton negative emissions. The Power to Heat Ratio ( ) (before implementation with CCS) is the most determining factor for the CHP process performance after CCS integration. The most determining factor for the district heating network performance is the ratio between plant heat generation capacity and the peak demand for district heating. Each operational strategy investigated, had advantages and disadvantages. The fuel consumption will increase with the implementation of CCS regardless of the operating strategy, although to different extents. Also, most CHP plants will not be able to maintain the present heat delivery if integrated with CCS. Each district heating system is, however, unique and should be investigated in further detail.
Keywords: CCS; CHP; district heating; biomass; waste